CHANGES IN THE COMPOSITION OF THE POPULATION OF FERGANA REGION IN 1876-1917 - Abdulkhodi A. Khaydarov (International Scientific and Current Research Conferences, 2023)
This article discusses the changes in the composition of the population of Fergana region in 1876-1917. Annual reports show only the total population of the region. In the appendices, the list of male and female population living in the region and the total number of each population and their general location by uezd are expressed in statistical numbers.